THE ROLE OF THE PATEAN SUBDISTRICT ELEMENTARY SCHOOL PHYSICAL EDUCATION TEACHERS WORKING GROUP IN EDUCATION DEVELOPMENT - Yofan Andana; Dian Ayu Zahraini; Buyung Kusumawardhana (YLPK Mahardhika, 2026)
This study aims to analyze the role of the Physical Education Teachers’ Working Group (KKG) in elementary schools in Patean Subdistrict in the development of Physical Education instruction. The issue examined is the suboptimal utilization of the KKG as a professional forum for enhancing teacher competence and promoting innovation in Physical Education instruction. This study employed a descriptive qualitative approach with purposive sampling involving seven informants, consisting of the chairperson, executive members, and members of the KKG. Data were collected through interviews, observations, and documentation and were analyzed through data reduction, data presentation, and conclusion drawing. Data validity was ensured through triangulation and member checking. The results indicate that the KKG serves as a source of inspiration, a model, a motivator, a catalyst, and an evaluator in the development of learning. The KKG provides a platform for teacher collaboration to share experiences, develop instructional materials, enhance professional competence, and conduct periodic evaluations of learning. The constraints identified include limited time, teachers’ administrative workload, inadequate facilities and infrastructure, and suboptimal member participation. This study highlights the importance of strengthening KKG programs and providing continuous support so that the KKG can function more effectively as a professional learning community that contributes to improving the quality of Physical Education instruction in elementary schools.